Effect of Different Post Materials and Adaptability on Fracture Resistance and Fracture Mode in Human Endodontically Treated Teeth - Anutara Bhaktikamala; Wareeratn Chengprapakorn; Pravej Serichetaphongse (Hindawi Limited, 2022)
Objective. To investigate the effect of different post materials and adaptability on fracture resistance and fracture mode of endodontically treated teeth. Materials and Methods. Sixty extracted human mandibular premolars were selected and divided into 6 groups (n = 10) according to the restorative method after endodontic treatment: no ferrule presented and restored without fiber post (Group C), 2.0 mm ferrule presented and restored without fiber post (Group CF), restored with D.T. Light-Post (Group PDT), restored with anatomically customized D.T. Light-Post, relined with resin composite (Group ADT), restored with Hi-Rem prosthetic post (Group PHR), and restored with anatomically customized Hi-Rem prosthetic post, relined with resin composite (Group AHR). After restoring with core build-up materials, all specimens were loaded at 45° in a universal testing machine until failure. Visual inspection of all specimens for fracture modes was performed. The data were analyzed using one-way ANOVA, and the fracture mode was reviewed using the chi-square test. Results. Anatomically customized groups presented statistically significant higher fracture resistance than prefabricated groups and group C (P<0.05). Without post, group CF displayed significantly higher fracture resistance than group C (P<0.05). Group C, CF, PDT, and PHR showed some specimens with unfavorable fractures. Conclusions. Anatomically customized posts presented highest fracture resistance among all groups. There was no significant difference in fracture mode across all groups.